O Bushidô como instrumento de divulgação da cultura japonesa no ocidente (Estudos Japoneses, 2010)
This article will focus on instrumental use of bushido by Inazo Nitobe during the Meiji Era (1868-1912)，especially during the Meiji Restoration，process whereby there were deep changes in the political scene, economic and social development of Japan, through the work Bushido - The Soul of Japan, used to disseminate the Japanese culture to Western nations to bring and improve relations between Japan and these nations. There will be a brief notes on the effects and uses，positive and negative，this work of Nitobe in the West in the years following its publication.